Import Dynamics and Demands for Protection - Hillberry, Russell; McCalman, Phillip (World Bank, Washington, DC, 2014)
What kinds of changes in foreign competition lead domestic industries to seek import protection? To address this question this paper uses detailed monthly U.S. import data to investigate changes in import composition during a 24-month window immediately preceding the filing of a petition for protection. A decomposition methodology allows a comparison of imports from two groups of countries supplying the same product: those that are named in the petition and those that are not. The same decomposition can be applied to products quite similar to the imports in question, but not subject to a petition. The results suggest that industries typically seek protection when faced with a specific pattern of shocks. First, a persistent positive relative supply shock favors imports from named countries. Second, a negative demand shock hits imports from all sources just prior to domestic industries' petition for protection. The relative supply shock is a broad one; it applies both to named commodities and to the comparison product group. The import demand shock, by contrast, is narrow, hitting only named products. The latter shock is also large: import growth over the two-year window is 15 percentage points lower in named products than in reference products, with most of this gap arising in the final two quarters before the petition. The negative import demand shock appears to be a key event in the run-up to the filing of a petition. It has been missed by previous studies using more aggregated data.